ONTOLOGICAL MISCONCEPTION IN MATHEMATICS TEACHING IN ELEMENTARY SCHOOLS - Imam Kusmaryono; Mochamad Abdul Basir; Bagus Ardi Saputro (IKIP Siliwangi and I-MES, 2020)
Elementary school teachers in Indonesia are required to master many subjects to be taught to their students. It is undeniable that the teachers’ mastery of knowledge (material) in some subjects inadequate. Therefore, it is worth to argue that there was a misconception in mathematics teaching in elementary schools. This research was designed using a qualitative approach. The participants of this study were 30 elementary school teachers in Semarang city area, Central Java province, Indonesia. The research data were obtained through questionnaires, and interviews. The purpose of the study was to discuss the types and causes of the misconception of mathematics teaching in elementary schools. Alternative solutions were also presented to problem-solving so that misconceptions do not occur anymore in mathematics teaching. The findings show that, teachers evenly experience types of misconceptions: (1) pre-conception, (2) under-generalization, (3) over-generalization, (4) modelling error, (5) prototyping error; and (6) process-object error in teaching mathematics in elementary schools. Some misconceptions have taken root and are difficult to remove, called